Discourse and the oppression of nonhuman animals: a critical realist account - Mitchell, Leslie Roy (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2009)
This work examines the use of nonhuman animals in the farming industry and seeks to understand why this practice takes place and what supports its continuation. The research is approached from a critical realist perspective and after a description of past and current practices in the industry, it uses abduction and retroduction to determine the essential conditions for the continuation of the phenomenon of nonhuman animal farming. One essential condition is found to be the existence of negative discourses relating to nonhuman animals and this aspect is examined in more detail by analyzing a corpus of texts from a farming magazine using Critical Discourse Analysis. Major discourses which were found to be present were those of production, science and slavery which construct the nonhumans respectively as objects of scientific investigation, as production machines and as slaves. A minor discourse of achievement relating to the nonhumans was also present. Further analysis of linguistic features examined the way in which the nonhumans are socially constructed in the discourses. Drawing on work in experimental psychology by Millgram, Zimbardo and Bandura it was found that the effects of these discourses fulfil many of the conditions for bringing about moral disengagement in people thus explaining why billions of people are able to support animal farming in various ways even though what happens in the phenomenon is contrary to their basic ethical and moral beliefs.
Keywords: Animal rights; Animal welfare -- Moral and ethical aspects; Critical realism; Critical discourse analysis; Animal industry -- Moral and ethical aspects; Livestock -- Social aspects; Human-animal relationships; Agriculture -- Moral and ethical aspects